Decoding the heterogeneity of liver-resident macrophages in chronic liver diseases: therapeutic responses to immunomodulatory strategies - Ouyang, Renbin; Li, Xiaocheng; Hao, Jianhua; Lin, Jie; Lan, Hui; Peng, Jing; Li, Xinmin; Tian, Zhiliang; Sun, Yu (Frontiers in Pharmacology, 2025)
Chronic liver diseases (CLDs), encompassing a spectrum of etiologies including metabolic dysfunction, alcohol abuse, and viral infections, represent a significant global health burden. The progression of these diseases to fibrosis, cirrhosis, and hepatocellular carcinoma is underpinned by complex immunological mechanisms in which liver-resident macrophages (LRMs) are central players. LRMs are not a monolithic population but a heterogeneous consortium of cells, primarily comprising embryonically-derived, self-renewing Kupffer cells and dynamically recruited monocyte-derived macrophages. These subsets, along with newly identified populations like lipid-associated macrophages and scar-associated macrophages, exhibit distinct origins, phenotypes, and functions that profoundly influence the trajectory of liver injury and repair. A new generation of immunomodulatory therapies is being developed to specifically target the pathways that govern LRM function. However, clinical responses to these agents have been variable, a phenomenon largely attributable to their differential effects on the diverse LRM subsets and the profound heterogeneity of the patient population. This review elucidates the complex heterogeneity of LRMs in the context of different CLDs. We dissect the mechanisms by which emerging immunomodulatory therapies—including PPAR agonists, chemokine receptor antagonists, and intracellular signaling inhibitors—alter the balance, phenotype, and functional output of distinct LRM populations. By integrating findings from preclinical models with outcomes from recent clinical trials, we illustrate how the specific modulation of LRM subsets correlates with therapeutic efficacy or failure. Furthermore, we discuss the critical role of LRMs in the progression to hepatocellular carcinoma and the implications for immune checkpoint inhibitor therapies. Finally, we outline the key challenges in translating these findings into clinical practice and highlight future research priorities, emphasizing the need for single-cell technologies, investigation of the gut-liver axis, and development of combination therapies. A deeper understanding of LRM biology is paramount to advancing a precision medicine approach, ultimately paving the way for more effective and personalized treatments for patients with CLD.